KARAKTERISTIK EKSTERIOR DAN UKURAN TUBUH KAMBING KOSTA JANTAN DAN BETINA DI CIRUAS, BANTEN - , ROSI PUTRI ABRIANTI; , Prof. Ir. I Gede Suparta Budisatria, M.Sc., Ph. D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The research was conducted to identify the exterior characteristics and body size of male and female Kosta goats at Ciruas, Banten. Fourty eight of male and female Kosta goats aged at less than one year (0-<12 months) and more than one year old (>12 months) were observed in this study. Direct observation and measurement were applied to collect all information required. Bandage tape, ruler and scales were used to measure the body size of goats, which consisted of hearth girth, chest width and chest depth, rump height and width, withers height, body length, head index and body weight. Student T-test was used to analyze the differences of body size between male and female goats. The result indicated that male and female Kosta goats had different exterior characteristics, such as the presence of whisker only for male goats and longer horn for male gats compared to female. Male Kosta goats at 0-12 months old had longer chest width, longer rump width, and higher body weight compared to female (P<0.05), it was 25.71Â±1.47 vs 13.69Â±0.89 cm